Understanding heart failure: pathophysiology and approach to therapy. Issue 2 (February 2021) - Laurence, Craig; Burch, Michael
Abstract: Heart failure during childhood is a final common pathway resulting from a range of causes. Diagnosis and management are challenging, and the evidence base for therapy is significantly smaller than in the adult literature. Where evidence is lacking, understanding of the underlying pathology is helpful to determine which treatment strategies are likely to bring most benefit. The clinical and haemodynamic features of heart failure arise from both the initial insult and the subsequent neurohormonal response, which, although beneficial in the short-term, is ultimately deleterious. Initial optimal management is focused on determining the aetiology and then achieving haemodynamic stability along with euvolaemia. Subsequent management includes specific treatment of the underlying aetiology if remediable, as well as arresting the maladaptive neurohormonal cascade. Additional goals include facilitation of adequate growth and development, and provision of psycho-social support for the patient and their family. Although pharmacologic management is relatively unchanged in recent years, a few new agents have shown promise for improved outcomes. Mechanical support options continue to evolve, although challenges remain, particularly in small infants. For children with severe heart failure without a reversible aetiology and recalcitrant to pharmacologic therapy, transplantation provides good quality of life. However, although outcomes continue to improve, it does not offer normal life expectancy. A multi-disciplinary approach, and effective communication, remain key in caring for these complex children and their families. This short review gives an overview of current practice highlighting the principles which underpin management for children with heart failure.